2002
DOI: 10.1029/2001jd001076
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of volatile organic compound emissions from ecosystems of China

Abstract: [1] Isoprene, monoterpene, and other volatile organic compound (VOC) emissions from grasslands, shrublands, forests, and peatlands in China were characterized to estimate their regional magnitudes and to compare these emissions with those from landscapes of North America, Europe, and Africa. Ecological and VOC emission sampling was conducted at 52 sites centered in and around major research stations located in seven different regions of China: Inner Mongolia (temperate), Changbai Mountain (boreal-temperate), B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
141
10
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 174 publications
(179 citation statements)
references
References 41 publications
21
141
10
1
Order By: Relevance
“…Isoprene emissions from a different leaf on the same tree were over 50 mg C g À1 h À1 by late afternoon, while A was similar for both the late morning (8.5 mmol m À2 s À1 ) and late afternoon (8.0-10.5 mmol m À2 s À1 ) measurements. Three of 21 Ficus species sampled during both wet and dry periods showed higher isoprene emission rates in the dry season by factors of 2-10 compared to wet season values reported in Klinger et al (2002). None of the 21 species showed significantly greater emission in the wet season (Table 1).…”
Section: Article In Pressmentioning
confidence: 85%
See 4 more Smart Citations
“…Isoprene emissions from a different leaf on the same tree were over 50 mg C g À1 h À1 by late afternoon, while A was similar for both the late morning (8.5 mmol m À2 s À1 ) and late afternoon (8.0-10.5 mmol m À2 s À1 ) measurements. Three of 21 Ficus species sampled during both wet and dry periods showed higher isoprene emission rates in the dry season by factors of 2-10 compared to wet season values reported in Klinger et al (2002). None of the 21 species showed significantly greater emission in the wet season (Table 1).…”
Section: Article In Pressmentioning
confidence: 85%
“…Emission of this compound is sometimes light dependent as well, although this was not determined here. Monoterpene emissions (1.2 mg C g À1 h À1 ) were also detected from F. fistulosa, whereas Klinger et al (2002) observed very little from this species. However, low levels of monoterpenes (primarily a-pinene and limonene) were also detected in the LAN GEMS blanks prior to emission sampling, indicating that GEMS carryover artifacts may have induced a 10-50% positive bias in calculated monoterpene emission rates from this species.…”
Section: Article In Pressmentioning
confidence: 94%
See 3 more Smart Citations